Integrative Network Pharmacology and Molecular Docking Analysis of Tinospora crispa L. for Breast Cancer Therapy - Dewi, Mirnawati; Ariefin, Mokhamat; Yolan Kalalinggi, Septaria; Andini, Novelia; Jipasca, Elon (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2026)
Breast cancer remains one of the leading mortality causes of disease related to cancer. Therefore, it is necessary to explore novel alternative therapeutic, particularly through the utilization of plant-derived natural product. Tinospora crispa L. contains diverse bioactive compounds with reported antioxidant and anticancer activities. This study integrates network pharmacology and molecular docking approaches to elucidate the molecular mechanisms of T. crispa against breast cancer. A total of 72 overlapping targets were identified between T. crispa compounds and breast cancer-related proteins, forming a highly interconnected PPI network consisting of 72 nodes and 340 edges. Clustering and enrichment analyses revealed that second cluster was significantly associated with cancer-related pathways, including AKT1, MAPK, and EGFR. The compound–protein–pathway network demonstrated two compound from T. crispa, apigenin and cycloeucalenone, possessed the highest degrees, suggesting their central regulatory roles. Molecular docking further confirmed these findings, showing that cycloeucalenone exhibited the strongest binding affinity toward EGFR and AKT1 through extensive hydrophobic interactions, whereas apigenin bound more stably to MAPK3 via multiple hydrogen bonds and hydrophobic interactions. These findings indicate that T. crispa compounds may exert anticancer effects by modulating multiple oncogenic pathways, supporting their potential development as multi-target agents in breast cancer therapy.